Performatividade E Subjetividade:: Paralelas Que Se Cruzam Na Análise De Um Discurso Médico Do Século XIX (PERcursos Linguísticos, 2023)
Our objective is to analyze the relation between the Medicine’s scientific discourse and it’s practice as it’s seen in a Manual localized in the archive of Museu de História da Medicina de Porto Alegre. We engage the analysis with the Manual de saúde ou medicina popular (1860), from François-Vicent Raspail, choosing Performativity and Subjectivity as analytical categories resulted from the dialogue between Austin (Philosophy of Language) and Benveniste (Linguistics of Enunciation). We opted for an analysis of the tenth chapter from the First Part, entitled “CAPITULO X - Meios preservativos e curativos contra as causas moraes de nossas doenças. ”. The primary results indicate that not only the dialogue between the authors and their concepts is possible, but it can also be prolific for an analysis of the Sub and Adjacency of the (medical) discourse.